Faktor-Faktor yang Mempengaruhi Loyalitas Konsumen Produk Jims Honey - Ririn Oktaviani; Atik Lusia (Jurnal Ilmiah Aset, 2022)
This research aims to analyze the factors that influence consumer loyalty for Jims Honey products at the Jimshoney_Klaten09 Online Shop. Data collection through questionnaires. The number of samples used is 125 consumers by using purposive sampling method. The data analysis technique used multiple linear regression analysis. The test results show that product quality does not affect consumer loyalty, while service quality, price and brand image have a significant effect on consumer loyalty.